2015
DOI: 10.1063/1.4921540
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional kinetic Monte Carlo simulations of diamond chemical vapor deposition

Abstract: A three-dimensional kinetic Monte Carlo model has been developed to simulate the chemical vapor deposition of a diamond (100) surface under conditions used to grow single-crystal diamond (SCD), microcrystalline diamond (MCD), nanocrystalline diamond (NCD), and ultrananocrystalline diamond (UNCD) films. The model includes adsorption of CH x (x = 0, 3) species, insertion of CH y ( y = 0-2) into surface dimer bonds, etching/desorption of both transient adsorbed species and lattice sidewalls, lattice incorporation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 32 publications
0
34
0
2
Order By: Relevance
“…Following to Ivanov et al this may indicate that the etched C d H 2 molecules are probably adjacent to other C d H 2 units on a flat face, and that its removal requires a higher energy to break C–C bonds. We can add to this information that the activation energy of 48 kcal mol −1 was deduced the kinetic Monte Carlo modeling of diamond growth, while recently, Glowacki et al modeled CH 3 dissociation from the diamond surface by molecular dynamics (MD) simulations found the free energy of activation of 35 kCal mol −1 for CH 3 dissociation at the diamond surface. Our measured activation energies seem to be in agreement with those two recent calculations.…”
Section: Resultsmentioning
confidence: 99%
“…Following to Ivanov et al this may indicate that the etched C d H 2 molecules are probably adjacent to other C d H 2 units on a flat face, and that its removal requires a higher energy to break C–C bonds. We can add to this information that the activation energy of 48 kcal mol −1 was deduced the kinetic Monte Carlo modeling of diamond growth, while recently, Glowacki et al modeled CH 3 dissociation from the diamond surface by molecular dynamics (MD) simulations found the free energy of activation of 35 kCal mol −1 for CH 3 dissociation at the diamond surface. Our measured activation energies seem to be in agreement with those two recent calculations.…”
Section: Resultsmentioning
confidence: 99%
“…Diamond growth occurs at the gas-surface interface, and it is fair to note that there is still much work required to determine the extent of gas processing in the boundary layer immediately above the growing surface, and in the larger scale simulation of diamond growth from the gas phase. [125][126][127] Another valid question is the extent to which all the foregoing plasma chemical insights could be used to enhance the efficiency of the diamond CVD process. Efficiency can be assessed in several ways.…”
Section: A Prospective Viewmentioning
confidence: 99%
“…In a recent kinetic Monte Carlo modelling study of diamond growth under CVD conditions [37], it was found that good agreement with observed rates of growth could be found when assuming a rate constant for etching provided with an Eyring expression together with a temperature-independent free energy of activation of 200 kJ mol −1 (48 kcal mol −1 ). While this is larger than the values shown in table 5, it should be noted that this value in fact corresponds to the activation free energy for loss of an adsorbed ‘carbon’, which is typically present as a ─CH 2 group inserted into a surface C–C bond.…”
Section: Molecular Dynamics Simulations Of –Ch3 Dissociation At the Dmentioning
confidence: 90%